1970
DOI: 10.1002/hlca.19700530848
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Nonbonding Orbitals in Carbonyls

Abstract: Zusammenfassung. In Dicarbonylen wie Glyoxal oder Benzochinon bilden die nichtbindenden Sauerstofforbitale delokalisierte Molekelorbitale mit verschiedenen Energien. Wir berichten iiber EHT-und CNDO/Z-Berechnungen einiger Dione und Trione. Die berechnete Aufspaltung zwischen den Nnichtbindenden 0 Kombinationen wird auf der Grundlage der u through-space 1) und H throughbond )) Wechselwirkung analysiert. Bei den tiefliegenden nichtbindenden Orbitalen der Carbonylgruppen scheint der zweite Faktor zu dominieren. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1971
1971
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Swenson and Hoffmann, using CNDO calculations, have concluded that the interaction which removes the n orbital degeneracy is a through-bond interaction with the carbons. 30 In n general sense, if the interaction were through-space instead of through-bond, then bringing the oxygens spatially closer shoui<l increase the na -nb separation. Since this separation does not increase when the oxygens are spatially closer in the ci~ form, our results support a through-bond interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Swenson and Hoffmann, using CNDO calculations, have concluded that the interaction which removes the n orbital degeneracy is a through-bond interaction with the carbons. 30 In n general sense, if the interaction were through-space instead of through-bond, then bringing the oxygens spatially closer shoui<l increase the na -nb separation. Since this separation does not increase when the oxygens are spatially closer in the ci~ form, our results support a through-bond interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…2-Isocyanatopyridine could be obtained only as dimer"'; and 2-isocyanato-3-methylpyridine (2) is stable only in its dimeric form (3), m. p. 212-215°C. This dimer (3) is obtained in quantitative yield by reaction of 3-methyl-2-pyridinamine with diphenyl carbonate via the intermediates ( I ) and (2).…”
Section: Pyridine Pyrimidine and Pyrazine Derivatives With An Isocymentioning
confidence: 99%
“…Finely powdered s-triazinamine (0.1 mol) is suspended in a mixture of oxalyl chloride (0.3-0.5 mol per amino group) and anhydrous toluene or chlorobenzene (1-2 mol) [but distilled thiophane dioxide for ( 2 ) ] , and the mixture is boiled under reflux until evolution of gas is complete (7-8 h). After filtration and removal of solvent by distillation, the residue is distilled in a vacuum.…”
Section: Isoc Yanato-s-triazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…We will show how a change in these interactions with rotation influences the geometric and conformational properties of the acetal segment. This procedure has been extensively used in the theoretical analysis of the interaction of nonbonding orbitals in different kinds of molecules along with EHT and C N D 0 / 2 semiempirical methods (19,20). Through-space and through-bond orbital interactions of lone pairs in an antiperiplanar conformation are analyzed using a simple perturbation molecular orbital (PMO) method (21) in the first part of the paper.…”
Section: Introductionmentioning
confidence: 99%